Control of the Light Interaction in a Semiconductor Nanoparticle Dimer Through Scattering Directionality - R. Vergaz; J. F. Algorri; A. Cuadrado; J. M. Sanchez-Pena; B. Garcia-Camara (IEEE Photonics Journal, 2016)
Dimers of nanoparticles are very interesting for several devices due to the possibility of obtaining intense light concentrations in the gap between them. A dynamic control of this interaction to obtain either the maximum or minimum light through interferential effects could be also relevant for a multitude of devices such as chemical sensors or all-optical devices for interchip/intrachip communications. Semiconductor nanoparticles satisfying Kerker conditions present an anisotropic scattering distribution with a minimum in either the forward or the backward direction and prominent scattering in the contrary direction. The reduction or enhancement of the electromagnetic field in a certain direction can minimize or maximize the interaction with neighboring nanoparticles. In this paper, we consider a dimer of nanoparticles such that each component satisfies each one of the Kerker conditions. Depending on the arrangement of the nanoparticles with respect to the impinging light direction, we can produce a minimum or a maximum of the electric field between them, reducing or maximizing the interferential effects. The strong dependence of the directional conditions with external conditions, such as the incident wavelength, can be used to dynamically control the light concentration in the gap.